PROFITABLITY AND LIQUIDITY ON CORPORATE VALUE THROUGH DIVIDEND POLICY AS INTERVENING VARIABEL: EMPIRICAL STUDY ON ISLAMIC CAPITAL MARKET - Sutrisno, Sutrisno; Panuntun, Bagus (Buletin Studi Ekonomi; VOL.25.NO.2.AGUSTUS 2020DO - 10.24843/BSE.2020.v25.i02.p05, 2020)
The purpose of this study is to examine the effect of profitability and liquidity on dividend policy and firm value. It also examines the role of dividend policy as an intervening variable between profitability and liquidity on firm value. Firm value is measured by Tobin's Q, dividend policy is measured by dividend payout ratio (DPR), profitability is measured by return on assets (ROA) and liquidity is measured by current ratio (CR). The population of this study is companies registered in List of Sharia Securities consisting of more than 300 companies. Samples were taken as many as 100 companies with a purposive sampling method. The observation period is 3 years (2016-2018). To test hypotheses using multiple regression analysis. The result shows that profitability is significant and positively effect on dividend policy, while liquidity does not affect on dividend policy. Profitability and dividend policy have a positive and significant effect on firm value, while liquidity has no effect on firm value. Another result of dividend policy is able to be as an intervening effect on profitability of firm value but not as an intervening liquidity relationship to firm value.